2001
DOI: 10.1016/s0212-6567(01)78859-2
|View full text |Cite
|
Sign up to set email alerts
|

Estudio multicéntrico sobre adhesión al tratamiento antibiótico en población infantil en atención primaria

Abstract: Only half the children complied correctly with the treatment indicated. Pre-school children, those with parents or carers over 40 and those with a prescription of under three daily doses followed the treatment better. These factors need to be borne in mind by paediatricians when they prescribe an antibiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…Nevertheless, many studies in paediatric patients proved non-adherence to treatment of chronic diseases to even exceed the level of 50%. For example, adherence in paediatric patients with Attention Deficit/Hyperactivity Disorder was only 39.9% [ 21 ], whereas out of 2244 Spanish children prescribed antibiotics, only 46.5% adhered adequately [ 22 ]. Having this data in mind it would be fair to say that survey participants underestimated the overall prevalence of non-adherence in paediatric patients, providing the average number below 30%, and close to 1/5 of respondents believing that non-adherence occurs in up to 10% of the paediatric patients only.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many studies in paediatric patients proved non-adherence to treatment of chronic diseases to even exceed the level of 50%. For example, adherence in paediatric patients with Attention Deficit/Hyperactivity Disorder was only 39.9% [ 21 ], whereas out of 2244 Spanish children prescribed antibiotics, only 46.5% adhered adequately [ 22 ]. Having this data in mind it would be fair to say that survey participants underestimated the overall prevalence of non-adherence in paediatric patients, providing the average number below 30%, and close to 1/5 of respondents believing that non-adherence occurs in up to 10% of the paediatric patients only.…”
Section: Discussionmentioning
confidence: 99%
“…Silvestre- Busto et al (2001), in a study comparing 6 indirect methods to evaluate therapy adherence, observed that the MGT underestimates the number of good adherents and overestimates the number of non-adherents by 7.9%. Notwithstanding, the MGT remains one of the best methods for assessing adherence, and is very reliable when nonadherent patients affirm this status.…”
Section: Discussionmentioning
confidence: 99%
“…Esta asociación también se ha observado en estudios previos 13,15,25 . Entre los motivos de incumplimiento, referidos por los padres, se incluyen la mejoría clínica y la presencia de efectos secundarios, que también se han identificado en estudios previos como causas más frecuentes de la no cumplimentación terapéu-tica 11,12 .…”
Section: Características De Los Participantesunclassified